Kenya : a natural outlook : geo-environmental resources and hazards - Paron, Paolo; Olago, Daniel O.; Omuto, C. (Christian) (Developments in earth surface processes, 2013)
This book aims at updating the holistic view on Kenya's natural environment and resources. It provides a sound scientific introduction to this country's physical and socioeconomic setting and its evolution through time.